Literacy and Intention to Pay Zakat - Rizaldi Yusfiarto; Ananda Setiawan; Septy Setia Nugraha (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
Zakat is a crucial instrument in Indonesian economic growth. It is considered vital because it can mobilize assets owned for economic growth by empowering certain groups in society, but Indonesian potential cannot be appropriately maximized. Empirically intention is a determining factor changes in muzakki behavior, influenced by muzakki's knowledge and attitude. The purpose of this study is to explore and examine how much impact the zakat literacy among Indonesian Muslims has on the intention to pay zakat. This study also analyzes the intention to pay zakat when viewed from the level of factors in the theory of planned behavior. This research involves structural equation modeling (SEM) approach, which is done through AMOS software, with a sample of 280 muzakki. The results of this study stated the hypothesis that was tested as a whole was accepted, so that it can be concluded the higher level of attitude, subjective norms, and literacy about zakat owned by muzakki it will have implications for the higher intention of muzakki in his compliance zakat paying